2011
DOI: 10.5089/9781455218035.001
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Bank Credit in Emerging Market Economies

Abstract: We examine changes in bank credit across a wide range of emerging market economies during the last decade. The rich time-series and cross-section information allows us to draw broader lessons compared to many existing researches, which focus on a specific set of emerging market economies or on shorter time periods. Our results show that domestic and foreign funding contribute positively and symmetrically to credit growth. The results also indicate that stronger economic growth leads to higher credit growth, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 2 publications
(2 reference statements)
6
22
0
Order By: Relevance
“…In light of this result, one can say that liquidity surpluses encourage banks to offer a variety of lending products. This finding is consistent with Ahmed et al (2009); Ivanović (2016); Stepanyan and Guo (2011) where they found a strong positive relationship between the rise in banks liquidity and increase in consumer loans. 2.…”
Section: Long-run Elasticitysupporting
confidence: 91%
See 1 more Smart Citation
“…In light of this result, one can say that liquidity surpluses encourage banks to offer a variety of lending products. This finding is consistent with Ahmed et al (2009); Ivanović (2016); Stepanyan and Guo (2011) where they found a strong positive relationship between the rise in banks liquidity and increase in consumer loans. 2.…”
Section: Long-run Elasticitysupporting
confidence: 91%
“…The authors found that interest rate has a positive effect, while unemployment rate exerts a negative impact on consumer lending. Stepanyan and Guo (2011) investigated the relationship between macroeconomic activities and consumer loans in Middle Eastern and North African countries using quarterly data. The study concluded that GDP growth has a positive effect on consumer lending.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, it speaks to a growing literature on the determinants of bank credit growth to the private nonfinancial sector, particularly in EMEs. Stepanyan and Guo () find that domestic deposit growth and non‐resident liability growth contribute to credit growth. They also find that stronger economic growth, higher inflation, and loose domestic and global monetary policies tend to increase domestic credit availability in the EMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, we interact the growth of non‐resident liabilities with the four‐period‐lagged share of non‐resident liabilities to private sector total credit ( Shr NRL c , t − 4 ). As explained by Stepanyan and Guo (), weighting the domestic and foreign funding variables by their respective shares helps control for the overall importance of these types of funding within a country.…”
Section: Empirical Specificationmentioning
confidence: 99%
“…The impact of capital and the size of banks on lending banks is expected to be positive. While GDP is expected to be positive and inflation is expected to be negative on lending banks (Bebczuk et al, 2011;Stepanyan & Guo, 2011;Pontines & Siregar, 2012;Silalahi, Wibowo, & Nurlian, 2012;Allen, Jackowicz, & Kowalewski, 2013;Cull & Pería, 2013;De Haas & Van Lelyveld, 2014).…”
Section: |mentioning
confidence: 99%